Preparation and Characterization of (PMMA-PVC-MWCNTs) Nanocomposite for EMI Shielding Application - Hatam Mohsin Shareef (Journal of Global Pharma Technology, 2016)
The (PVC-PMMA-MWCNTs) nanocomposites have prepared by Solution cast technique with different concentrations of CNTs (0, 0.5, 1, 1.5, 2, 2.5), casted in a clean glass plate. The structures of nanocomposites have been studied. The structural properties include Fourier Transform infrared spectroscopy (FTIR), scanning electron microscope (SEM). The effect of radar in the range (8-12) GHZ on (PVC-PMMA-MWCNTs) nanocomposite films, were studied as applications for shielding from Electromagnetic Interference (EMI), and has been noticed that the shielding effectiveness increases with the increase of concentration of MWCNTs.Keywords: Blend polymer, Cast method, MWCNTs, PMMA, PVC.